PENGARUH MODEL PEMBELAJARAN SQ3R (SURVEY, QUESTION, RECITE, REVIEW) TERHADAP HASIL BELAJAR SISWA KELAS IV SEKOLAH DASAR NEGERI 1 GISTING, TANGGAMUS - Lestari, Yulita Dwi; Pangestu, Deviyanti (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2020)
This study aims to determine the effect of using the SQ3R learning model (Survey, Question, Read, Recite, Review) on student learning outcomes. The problem in this study is the low student learning outcomes. This research uses purposive sampling. The instrument used in this study used non-tests and tests. The results of data analysis showed that there was an influence on the use of the SQ3R learning model (Survey, Question, Read, Recite, Review) on the learning outcomes of Grade IV students of SDN 1 Gisting. This is indicated by the average value of student learning outcomes who follow learning using the SQ3R learning model (Survey, Question, Read, Recite, Review) in the experimental class is higher than the average value of student learning outcomes who do not use the SQ3R learning model ( Survey, Question, Read, Recite, Review) in the control class.